ANALISIS KEBUTUHAN PENGEMBANGAN E-MODULE DENGAN PENDEKATAN UNIVERSAL DESIGN FOR LEARNING (UDL) PADA MATERI SISTEM EKSKRESI MANUSIA UNTUK PESERTA DIDIK INKLUSI TINGKAT SMA - Wirdhatul Jannah; Rahmatika, Helsa; Syamsurizal; Rahmi, Fitri Olvia (CV. Jendela Gagasan, 2025)
This study aims to analyze the need for e-module development using the Universal Design for Learning (UDL) approach on the human excretory system material for inclusive high school students. The type of research used is descriptive quantitative. Data collection techniques were carried out by interviewing Biology teachers, administering a learning style identification questionnaire, and administering a questionnaire for analyzing the needs of teaching materials development. The research subjects consisted of biology teachers and inclusive students of grade XI. Based on observations and questionnaires at SMAN 1 Sungayang, it was found that inclusive students (regular students and students with special needs) face various obstacles in learning biology, especially for physically disabled students. These obstacles include limited adaptive teaching materials, the dominance of textbooks, and diverse learning styles that have not been facilitated. The results of the interviews showed that inclusive students need flexible teaching materials and support independent learning. Based on the learning style identification questionnaire, students have diverse learning styles. Most have visual learning styles (14%), auditory (9%), kinesthetic (2%), and combined (75%). The results of the needs analysis show that (87%) students experienced difficulties in learning Biology, including choosing material on the human excretory system, namely (31%). A total of 69% of students stated they had never used an e-module with a UDL approach. However, 100% of students agreed with the development of a UDL-based e-module. The analysis indicates that research is needed on the development of a Universal Design for Learning (UDL)-based e-module that can present material flexibly, visually, interactively, and inclusively.